ANALISIS HASIL ASESMEN SUMATIF AKHIR SEMESTER GANJIL DAN TINGKAT KESUKARAN BUTIR SOAL MATEMATIKA KELAS VII TAHUN PELAJARAN 2025/2026 - Zulkarnain; Salnia Ramadani (Tautologi: Journal of Mathematics Education, 2026)
This study aims to analyze the results of the Assessment and the level of difficulty of the Final Summative Assessment items of the Odd Semester in Mathematics for seventh grade students in the 2025/2026 academic year. A descriptive quantitative method was used, using the level of difficulty and frequency distribution techniques. The research subjects consisted of 138 seventh grade students in five classes (7A, 7B, 7C, 7D, and 7E). The assessment instrument consisted of 20 multiple-choice questions. The results showed that the overall average score was 43.51 with a standard deviation of 18.03. The mastery level was only 28.3% (39 students completed), while 71.7% (99 students) did not reach the KKTP threshold set by the school (score 55). Analysis of the level of difficulty of the questions showed that items 10 and 18 had the lowest percentage of correct answers, indicating the highest level of difficulty. This study recommends the application of contextual and meaningful learning approaches and interactive media to improve students' conceptual understanding.